Disease-mongering through clinical trials. (June 2015) - González-Moreno, María; Saborido, Cristian; Teira, David
Abstract: Our goal in this paper is to articulate a precise concept of at least a certain kind of disease-mongering, showing how pharmaceutical marketing can commercially exploit certain diseases when their best definition is given through the success of a treatment in a clinical trial. We distinguish two types of disease-mongering according to the way they exploit the definition of the trial population for marketing purposes. We argue that behind these two forms of disease-mongering there are two well-known problems in the statistical methodology of clinical trials (the reference class problem and the distinction between statistical and clinical significance). Overcoming them is far from simple. Highlights: We articulate a precise concept of certain types of disease-mongering. Behind disease-mongering we find the reference class problem and the distinction between substantive and statistical significance. Two cases studies illustrate our claims: the marketing of benzodiazepines and statins.